Comparison of micro-flow imaging and contrast-enhanced ultrasound in monitoring microwave ablation of papillary thyroid carcinoma: efficacy, safety, and cost-effectiveness - Li, Xiangyu; Zhuang, Min; Hu, Ziyue; Xie, Xiaoxiao; Cui, Likun; Lu, Man (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the value of micro-flow imaging (MFI) in monitoring ultrasound-guided microwave ablation (MWA) of papillary thyroid carcinoma (PTC) by comparing it with contrast-enhanced ultrasound (CEUS).MethodsThis study was conducted on 83 malignant nodules from 79 papillary thyroid carcinoma (PTC) patients treated between June 2022 and September 2023. These cases were divided into a control group (n=37) and an observation group (n=42) based on different guidance modalities during microwave ablation (MWA). The observation group underwent MFI monitoring, while the control group received CEUS monitoring. Clinical parameters were systematically compared between groups, including: 1) baseline clinical characteristics, 2) two-dimensional ultrasound features, 3) vascular patterns (MFI/CEUS), 4) tumor volume (V), 5) volume reduction rate (VRR), 6) postoperative complications, and 7) patient satisfaction outcomes.ResultsAll patients successfully underwent ablation. During multiple follow-ups post-MWA, no local recurrence or distant metastasis was observed in either group, and changes in V and VRR were similar (p > 0.05). Consistency was also observed in the number of ablations, ablation time, and postoperative complications between the two groups (p > 0.05). However, the MFI group had lower treatment costs and operation time compared to the CEUS group (p < 0.05), and patients in the MFI group reported higher satisfaction with the procedure (p < 0.05).ConclusionThe effectiveness and safety of MFI monitoring during PTC ablation are similar to those of CEUS, with the added advantages of lower costs and greater patient satisfaction, making MFI a preferable option for patients.